Enhancement of pH values stability and photo-fermentation biohydrogen production by phosphate buffer - Siyi Guo (Bioengineered, 2020)
The main aim of this study was to investigate the effects of the initial pH values of the buffer on photo-fermentation biohydrogen production. Hydrogen production and the kinetics of it under different initial pH values were analyzed. Effects of initial pH values on reducing sugar consumption, hydrogen production rate, and byproduct production were evaluated at initial pH values of 5–7. The results showed that initial pH values of phosphate buffer had a significant effect on biohydrogen production via photo-fermentation. With the initial pH value of phosphate buffer at 6.0, the cumulative hydrogen production reached its maximum, 569.6 mL. The maximum hydrogen production rate was 23.96 mL/h at the initial pH value of 6.5. With the initial pH values at 5.0 and 7.5, the maximum hydrogen production rates were becoming lower, only 5.59 mL/h and 5.42 mL/h, respectively. And with the increase in pH values, the peak period of hydrogen production was gradually delayed, indicating that the alkaline environment had a negative effect on the ability of photosynthetic bacteria. This study revealed the influence of phosphate buffer initial pH values on the biohydrogen production via photo-fermentation and aimed to provide a scientific reference for further improving the theory and technology for biohydrogen production from biomass.